ANALISA HUKUM STATUS KEPEMILIKAN TANAH BERUPA SURAT KETERANGAN GANTI KERUGIAN (SKGR) BAGI WNI YANG PINDAH KEWARGANEGARAAN - Ricki Musliadi; Ulfia Hasanah (Lembaga Marwah Rakyat, 2023)
The Riau Provincial Government through the Head of Village (Lurah) has issued a Land Certificate (SKT) and a Certificate of Compensation (SKGR) as documents used by land owners to apply for land ownership registration in reference to the provisions of Articles 23 and 24 of Government Regulation Number 24/1997 on Land Registration. However, referring to Government Regulation Number 24/1997 on Land Registration, it is not explicitly stated that there is an obligation for Lurah to issue those types of land ownership certificate mentioned above. In previous years, the public's interest to process land ownership certificates in the Regency/City Land Agency in Riau is still lacking. The people are under the impression that land ownership certificate in the form of SKGR is enough to justify the legality of the land ownership. Referring to that condition, there was a case in Riau Province in which an Indonesian citizen who had land ownership status only in the form of SKGR happened to renoune his citizenship. Based on the problems stated above, the author would examine the legal analysis of land ownership in the form of SKGR for Indonesian citizens who renounced citizenship. The methodology used in this research is normative law study. Keywords: Land, SKGR, Citizenship